2003
DOI: 10.1182/blood-2002-02-0603
|View full text |Cite
|
Sign up to set email alerts
|

LF 15-0195 immunosuppressive agent enhances activation-induced T-cell death by facilitating caspase-8 and caspase-10 activation at the DISC level

Abstract: The deoxyspergualin derivative LF 15-0195 has demonstrated some efficacy in animal models of autoimmune and graftversus-host diseases and is currently tested in clinics. The molecular mechanisms of LF 15-0195 immunosuppressive activity remained unknown. We show that exposure to LF 15-0195 sensitizes Jurkat T cells to apoptosis induced by an agonistic anti-CD95 antibody (CH11 clone) and by the cytokine TNF-related apoptosisinducing ligand. LF 15-0195 does not demonstrate any significant effect on the postmitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…15,28 LF15-0195 can also sensitize cells to activation-induced cell death by a Fas-dependent mechanism that triggers the activation of caspases. 33 One of our initial hypotheses concerning this model was that LF15-0195 acts via the inhibition of NF-B activation in glomerular epithelial cells to modify the pathway of a putative nephrotoxic factor. This hypothesis was supported by the observation of an increase in NF-B expression in kidney biopsies of patients with INS recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,28 LF15-0195 can also sensitize cells to activation-induced cell death by a Fas-dependent mechanism that triggers the activation of caspases. 33 One of our initial hypotheses concerning this model was that LF15-0195 acts via the inhibition of NF-B activation in glomerular epithelial cells to modify the pathway of a putative nephrotoxic factor. This hypothesis was supported by the observation of an increase in NF-B expression in kidney biopsies of patients with INS recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, LF15-0195 could sensitize cells to activation-induced cell death, thereby providing a model to understand how LF15-0195 can eliminate renal infiltrating cells or other pathologic populations. 33 A recent study showed that the injection of CD34 ϩ stem cells from patients with INS into immunocompromised mice triggered an albuminuria associated with the effacement of podocyte process in these animals. 42 We performed the inverse process of transferring cells with the capacity to block and control such pathogenic cells.…”
Section: Cd25mentioning
confidence: 99%
“…In turn, FADD recruits procaspase-8 to form the death-inducing signaling complex (DISC) in which caspase-8 is activated, thus leading to apoptosis (21)(22)(23). We and others (24,25) have shown that the Fas-mediated pathway may contribute, in a ligand-dependent or -independent manner, to the death of cells exposed to various stimuli, including anticancer drugs and immunomodulatory molecules (26). Whether resveratrol-induced apoptosis also implicates death receptors remains a controversial issue (10 -13).…”
mentioning
confidence: 99%
“…This mode of action would prevent NF-B from dissociating from its inhibitor and would sequester it in the cytoplasm to suppress its downstream effects in the nucleus of antigen presenting cells (APCs) and lymphocytes. Furthermore, it has been demonstrated that LF promotes activation-induced cell death (AICD) of T cells, a process that has been linked to the induction of tolerance (26). In addition, we have recently reported that LF significantly reduces the humoral immune response in both allograft and xenograft transplant models (27,28).…”
Section: Rapa and Lf Had A Synergistic Effect In Induction Of Donor-smentioning
confidence: 99%